Synthesis of furo[3, 4-c]quinolin-3(1H)-one derivatives through TMG catalyzed intramolecular aza-MBH reaction based on the furanones. Issue 22 (9th February 2015) - Yin, Dawei; Wang, Wei; Peng, Yangqiu; Ge, Zemei; Cheng, Tieming; Wang, Xin; Li, Runtao
Abstract : The first TMG catalyzed intramolecular aza-MBH reaction based on furanone derivatives for the construction of furo[3, 4- c ]quinolin-3(1 H )-ones scaffold. Abstract : The first TMG catalyzed intramolecular aza-MBH reaction based on furanone derivatives was developed and successfully applied in the synthesis of a novel fused heterocyclic scaffold, furo[3, 4- c ]quinolin-3(1 H )-ones in moderate to good yields.